Heating and cooling in flutdised bed furnace for heat treatment and industrial applications / Zuliah Aleakhber and Mohd. Nizam Jumaat - Aleakhber, Zuliah; Jumaat, Mohd. Nizam (Faculty of Mechanical Engineering, Universiti Teknologi MARA, 1995)
Fluidisation is a technique whereby gas or vapour passed through so that the mixture behave as a liquid and also have special significance when the solid is a catalyst to induce reactions in the fluidising medium. If a fluid is passed upward through a bed of solid with a velocity high enough for the particle to separate from another by small layer of fluid. The fluid may be either a liquid or gas. As the velocity of the fluid increases, the particles become suspended in the upward moving fluid. The point at which the particles just become suspended is the point at which the whole bed takes on the characteristics o f a liquid. The particles become freely supported in the fluid, the bed is solid to be fluidised. Then the total fluid frictional force on the particles is equal to the effective weight of bed. It is usually use in chemical industry because of: i. the intimate contact between solid and gas ii. the high rates of heat transfer iii. the uniform temperature within the bed iv. high heat transfer coefficients from the bed to the walls of the containing vessel Fluidisation is also used in the transport of particles that otherwise are difficult to handle, e.g. unloading of powdered cement from transport trucks. In metal industry Fluidised Bed Furnace are widely use for heat treatment, as heat treatment is the main process in metal industry to change the metal properties.